Challenges and choices for crime-fighting technology : federal support of state and local law enforcement - Schwabe, William, 1942- (MR (Series), 2001)
This report provides findings of a study of technology in use or needed by law enforcement agencies at the state and local level, for the purpose of informing federal policymakers as they consider technology-related support for these agencies.